الخصائص السيكومترية للنسخة الجزائرية لمقياس توقعات الكفاءة الذاتية العامة لدى تلاميذ المرحلة الثانوية - بوقصارة, منصور; زياد, رشيد (جامعة الوادي - University of Eloued, 2015)
تهدف الدراسة الحالية إلى تقويم الخصائص السيكومترية للنسخة الجزائرية لمقياس توقعات الكفاءة العامة لدى تلاميذ المرحلة الثانوية. اختيرت عينة قوامها 339 تلميذا وتلميذة، منهم 111 ذكور، و228 إناث. كما اختيرت عينة أخرى مختلفة عن العينة الأساسية مكونة من 69 تلميذا وتلميذة استخدمت للتحقق من الثبات بإعادة التطبيق. وللتأكد من ثبات المقياس تم استخدام أربع طرق، هي: معامل "ألفا كرونباخ"، والثبات بإعادة التطبيق، ومعامل "جتمان"، ومعامل "سبيرمان – وبراون" المصحح. كما تم التحقق من صدق المقياس من خلال: الصدق الظاهري، الصدق التمييزي للبنود الصدق المحكي (التلازمي)، وصدق التحليل العاملي الاستكشافي والتحليل العاملي التوكيدي. أكدت نتائج الدراسة على جودة الخصائص السيكومترية لمقياس توقعات الكفاءة الذاتية العامة في البيئة الجزائرية This study aims to evaluate the psychometric properties of the Generalized Self-Efficacy Expectations Scale- Algerian version (GES) for high school pupils. A selected sample of N=339 including 288 females and 111 males of high Shool pupils. Another sample was selected which was different from the basic sample consisting of N=69 males and females pupils used to test-retest reliability method. To evaluate the scale reliability four (04) ways were utilized: Gronbach’s alpha coefficient, the test-retest method, Guttman coefficient, and the spearman and Brown correction coefficient. The validity of scale was confirmed through several ways: the face validity, discriminant validity of items, concurrent validity, construct validity using exploratory and confirmatory factor analysis. The results of the study confirmed the quality of the psychometric properties of the Generalized Self-Efficacy Expectations Scale in the Algerian Environment
مقال بمجلة العلوم النفسية والتربوية 01-10-2015 جامعة الوادي
Keywords: الخصائص السيكومترية، التحليل العاملي التوكيدي، الكفاءة الذاتية العامة; psychometric properties, confirmatory factor Analysis, self -efficacy.